Penerapan Perawatan Sekoci Penolong Sesuai Standar Solas Di Kapal MT.Mitra Kemakmuran - Refaya Alwim Takainginan, Refaya; Rusman Rusman; Frastika Frastika (Politeknik Pelayaran Sulawesi Utara, 2022)
The purpose of this study was to determine whether the implementation of lifeboat maintenance on the ship was in accordance with existing procedures. This research was carried out during Marine Pratek (PRALA) aboard MT.Mitra Kemakmuran. The results of this study found that there were several factors causing the lifeboat not to function or when there was an obstacle when lowering the lifeboat. Before the crew entered the lifeboat, it was found that the FPD (Fall Preventer Device) of the right lifeboat was damaged (the rope almost broke) while it must be installed perfectly before the crew the ship enters the lifeboat during training or when lifeboat maintenance is carried out in accordance with SOLAS Chapter III Regulation 20. What can be done by crew members to improve lifeboat maintenance on board in accordance with the Safety Of Life At Sea (SOLAS) is to comply with all regulations that have been made. written in the standard without missing anything for any reason.